Tropical forages identification tool: A new companion for tropical forages selection tool - Cardoso, Juan Andrés (Bioversity International and the International Center for Tropical Agriculture, 2022)
There has been a recent explosion in the development of image recognition technology and its application to automated plant identification, so it is timely to consider its potential for the identification of tropical forages in the field. On many occasions, producers and researchers alike confuse forages with each other. This generates confusion, poor use and management of the forage resource, which might affect negatively livestock productivity. For this reason, we built the Tropical forages identification tool: a tool to assist ranchers and farmers to identify forages present on their farms or elsewhere based on images and an artificial intelligence model.